Agronomic perspective: exploring the diversity and potentialities of banana cultivation (Musa spp.) - Djair Alves da Mata; Daniel Alves da Mata; Valdeir de Souza Oliveira; Ivana Tito Sousa; Mirelly Miguel Porcino; José Roberto Santana da Silva; Romildo Araújo Macena; Elany Pereira Marques da Silva (Scientific Electronic Archives, 2024)
This article addresses the importance of banana cultivation (Musa spp.) in Brazil, focusing on its genetic diversity, economic potential, and challenges faced by producers. The bibliographic review conducted highlights the socio-economic relevance of bananas, their role in job creation and income generation, and their contribution to food security. Banana genetic diversity is a key point, offering varieties with distinct characteristics adapted to different environmental conditions. However, banana production faces significant challenges, such as pest and disease control, ensuring food quality and safety, and the need to promote sustainable agricultural practices. Collaboration among different actors in the production chain, including governments, research institutions, the private sector, and civil society, is essential to address these challenges and explore opportunities for sustainable development. Investing in research, innovation, and producer training is recommended, as well as promoting diversification of banana-derived products to add value to production and create new business opportunities. In summary, this article provides a comprehensive overview of banana cultivation in Brazil, highlighting its potential and challenges, and providing valuable insights for researchers, farmers, and policymakers.